Quantifying public radiation exposure related to lutetium-177 octreotate therapy for the development of a safe outpatient treatment protocol. Issue 2 (February 2015) - Olmstead, Craig; Cruz, Kyle; Stodilka, Robert; Zabel, Pamela; Wolfson, Robert
Abstract : Objectives: Radionuclide therapies, including treatment of neuroendocrine tumors with lutetium-177 (Lu-177) octreotate, often involve hospital admission to minimize radiation exposure to the public. Overnight admission due to Lu-177 octreotate therapy incurs additional cost for the hospital and is an inconvenience for the patient. This study endeavors to characterize the potential radiation risk to caregivers and the public should Lu-177 octreotate therapies be performed on an outpatient basis. Materials and methods: Dose rate measurements of radiation emanating from 10 patients were taken 30 min, 4, and 20 h after initiation of Lu-177 octreotate therapy. Instadose radiation dose measurement monitors were also placed around the patients' rooms to assess the potential cumulative radiation exposure during the initial 30 min–4 h after treatment (simulating the hospital-based component of the outpatient model) as well as 4–20 h after treatment (simulating the discharged outpatient portion). Results: The mean recorded dose rate at 30 min, 4, and 20 h after therapy was 20.4, 14.0, and 6.6 μSv/h, respectively. The majority of the cumulative dose readings were below the minimum recordable threshold of 0.03 mSv, with a maximum dose recorded of 0.18 mSv. Conclusion: Given the low dose rate and cumulative levels of radiation measured, the results support that an outpatient Lu-177 octreotate treatment protocol would not jeopardize public safety. Nevertheless, the concept of ALARA still requires that detailed radiation safety protocols be developed for Lu-177 octreotate outpatients to minimize radiation exposure to family members, caregivers, and the general public.